2022
DOI: 10.1093/oncolo/oyac053
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, Potentially Inappropriate Medications, and Drug-Drug Interactions in Vulnerable Older Adults With Advanced Cancer Initiating Cancer Treatment

Abstract: Purpose Polypharmacy is prevalent in older adults starting cancer treatment and associated with potentially inappropriate medications (PIM), potential drug-drug interactions (DDI), and drug-cancer treatment interactions (DCI). For a large cohort of vulnerable older adults with advanced cancer starting treatment, we describe patterns of prescription and nonprescription medication usage, the prevalence of PIM, and the prevalence, severity, and type of DDI/DCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 39 publications
2
19
1
5
Order By: Relevance
“…In comparison of five DDI programs, including Lexi-Interact, Micromedex, iFacts, Medscape and Epocrates, Lexi-Interact and Micromedex showed the best performance on accuracy and sensitivity ( Kheshti et al, 2016 ). Lexi-Interact was widely used in various diseases and different areas ( Ren et al, 2020 ; Dagdelen et al, 2021 ; Ramsdale et al, 2022 ). Meanwhile, Lexi-Interact was available in our health system, as such, pDDIs were reviewed using Lexi-Interact software in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison of five DDI programs, including Lexi-Interact, Micromedex, iFacts, Medscape and Epocrates, Lexi-Interact and Micromedex showed the best performance on accuracy and sensitivity ( Kheshti et al, 2016 ). Lexi-Interact was widely used in various diseases and different areas ( Ren et al, 2020 ; Dagdelen et al, 2021 ; Ramsdale et al, 2022 ). Meanwhile, Lexi-Interact was available in our health system, as such, pDDIs were reviewed using Lexi-Interact software in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Unlike many prior studies, we included over-the-counter and complementary medications, which are rarely accounted for but are often PIMs and/or are involved in PDIs. 30 In addition, we adjusted for confounding by indication by including patients' comorbidities and functional status as covariates in the multivariable models. In a recent systematic review, we demonstrated that most existing studies evaluated polypharmacy as a covariate or risk factor within a larger exploration of many potential risk factors, which may have created residual confounding issues and spurious associations between medication measures and treatment adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of our study is its understudied population: older adults with advanced cancer receiving treatment in community oncology (i.e., real‐world) practices who are at a high risk of cancer treatment adverse effects 13 . Unlike many prior studies, we included over‐the‐counter and complementary medications, which are rarely accounted for but are often PIMs and/or are involved in PDIs 30 . In addition, we adjusted for confounding by indication by including patients' comorbidities and functional status as covariates in the multivariable models.…”
Section: Discussionmentioning
confidence: 99%
“…For example, embedding the GO-PIM scale in EHRs to automate the detection of PIMs could make targeted "point-of-care" deprescribing feasible in the clinic, which in turn may be associated with a reduction in adverse outcomes. 51 Moreover, leveraging existing databases to identify interactions between PIMs and cancer therapies 63 could improve safety in older adults with blood cancers. eAppendix 1.…”
Section: Discussionmentioning
confidence: 99%